Comparative Pharmacokinetics of Gentamicin C1, C1a and C2 in Healthy and Infected Piglets - Eun-Young Kim; Tae-Won Kim; Elias Gebru Awji; Eon-Bee Lee; Seung-Chun Park (MDPI AG, 2024)
Gentamicin, an aminoglycoside antibiotic, is a mixture of therapeutically active C1, C1a, C2 and other minor components. Despite its decades-long use in pigs and other species, its intramuscular (IM) pharmacokinetics/pharmacodynamics (PKs/PDs) are unknown in piglets. Furthermore, the PKs of many drugs differ between healthy and sick animals. Therefore, we investigated the PKs of gentamicin after a single IM dose (10 mg/kg) in healthy piglets and piglets that were intranasally co-infected with Actinobacillus pleuropneumoniae and Pasteurella multocida (PM). The plasma concentrations were measured using validated liquid chromatography/mass spectrometry. The gentamicin exposure was 36% lower based on the area under the plasma concentration-time curve and 16% lower based on the maximum plasma concentration (Cmax) in the infected piglets compared to the healthy piglets, while it was eliminated faster (shorter half-life and larger clearance) in the infected piglets compared to the healthy piglets. The clearance and volume of distribution were the highest for the C1 component. C1, C1a and C2 accounted for 22-25%, 33-37% and 40-42% of the total gentamicin exposure, respectively. The PK/PD target for the efficacy of aminoglycosides (Cmax/minimum inhibitory concentration (MIC) > 10) could be exceeded for PM, with a greater magnitude in the healthy piglets. We suggest integrating this PK information with antibiotic susceptibility data for other bacteria to make informed antibiotic and dosage regimen selections against piglet infections.